Social Media and Marital Dynamics: A Qualitative Analysis of Impact on Communication, Trust, and Conflict among Couples in Jammu and Kashmir (UT) - Bilal Ahmad Mir; Sameer Maqbool Wani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Social media has revolutionized modern communication, profoundly affecting daily life, including marital relationships. While technology has enhanced connectivity, its influence on marriage can be complex. This study explores the interplay between social media use and marital satisfaction among Jammu and Kashmiri couples, focusing on communication, trust, and relationship quality. Using a qualitative case study approach with thematic analysis, insights from nine married couples across four districts in South Kashmir reveal varied experiences, highlighting both positive impacts and challenges such as emotional distance and conflict. The findings demonstrate that social media serves dual roles: maintaining family bonds across distances while potentially causing technoference, trust issues, and addiction when boundaries are absent. Successful couples employ open communication, transparency, and mutual boundary-setting to navigate digital challenges. The study emphasizes the need for balanced social media use within marriages and provides evidence-based recommendations for couples, counselors, and policymakers to foster healthy, resilient relationships in the digital age while considering the unique socio-cultural context of Jammu and Kashmir.